Viable Glycerol Carbonate Synthesis Through Direct Crude Glycerol Utilization from Biodiesel Industry - Indran, Vidhyaa Paroo; Anisah Sajidah, Haji Saud; Gaanty Pragas, Maniam; Yun Hin, Taufiq-Yap; Mohd Hasbi, Ab. Rahim (Springer, 2016)
Synthesis of organic carbonates specifically glycerol carbonate has become a major concern among researchers due to its interesting chemical properties. In this study, we report the direct utilization of two different sources of crude glycerol in glycerolysis reaction with urea for the synthesis of glycerol carbonate using potassium silicate containing boiler ash as a catalyst. The level of interference of moisture and methanol content in crude glycerol was studied by mimicking conditions in pure glycerol and it was found that moisture at 10 wt% significantly effects the conversion of glycerol while methanol at 5 wt% affects the selectivity towards glycerol carbonate. However, due to the low moisture and methanol content in crude glycerol, comparable yield % of glycerol carbonate with commercial pure glycerol as starting feedstock was noted. Besides, the study also found that the potassium methylate and sodium methylate used as catalysts for the commercial production of biodiesel can be also used as an effective catalyst for the synthesis of glycerol carbonate. The current approach is a near approach for a greener environment which proposes use of both catalyst and glycerol derived from waste sources.